Akibat Hukum Terhadap Surat Kuasa Membebankan Hak Tanggungan Pasca Keputusan Pailit - Troy Iversen Jayakusuma; Indra Yuliawan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study analyzes the legal validity of the Power of Attorney to impose Mortgage Rights executed after a bankruptcy decision.The research is based on a case study of the Commercial Court Decision of Semarang Number 11/Pdt.Sus-GLL/2023 in conjuction with previous related rulings. The background of this particularly when creditors attempt to secure their interest through unilateral legal actions after a bankriptcy declaration. This study aims to examine the legal consequences of post-bankruptcy Power of Attorney to impose Mortgage Rights execution and evaluate its compliance with Indonesian bankruptcy law and civil law priciples. The research employs a normative juridical method using statutory and case aaproaches. The findings indicate that the execution of Power of Attorney to impose Mortgage Rights and the subsequent establishment of mortgage rights after a bankruptcy decision are legally invalid. This is due to the debtor losing authority over their assets upon the declaration of bankruptcy, as regulated under Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. Besides that the action also violates the subjective conditions of the agreement in Article 1320 of the Civil Code and is an act against the law. The implication of this research emphasizes the importance of protecting the pari passu pro rata parte principle to ensure fairnessfor all creditos in the bankruptcy process.